1999
DOI: 10.1046/j.1365-3156.1999.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Fascioliasis: sonographic abnormalities of the biliary tract and evolution after treatment with triclabendazole

Abstract: SummaryDiagnosis of infection with the liver fluke Fasciola hepatica is usually difficult. Ultrasonography (US) might be a useful diagnostic alternative, and we assessed the value of sequential US in the diagnosis and monitoring of fascioliasis in 76 patients at baseline and for 60 days after treatment with triclabendazole. At baseline, biliary abnormalities were observed in 52 patients. Crescent-shaped parasites were seen in 11 patients; in 2 cases parasites were spontaneously moving and in 4 patients parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 26 publications
3
28
0
6
Order By: Relevance
“…Details on ultrasonographic methodology are published elsewhere. 28 Clinical evaluation and safety assessment. For close monitoring, patients were hospitalized at the Institute of Tropical Medicine 'Pedro Kouri' (IPK) during the first 7 days after treatment in order to allow prompt therapy if adverse events occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Details on ultrasonographic methodology are published elsewhere. 28 Clinical evaluation and safety assessment. For close monitoring, patients were hospitalized at the Institute of Tropical Medicine 'Pedro Kouri' (IPK) during the first 7 days after treatment in order to allow prompt therapy if adverse events occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Both species can host larvae of the trematode, but only the former has been found naturally infected in the island. Currently, only the curative aspect of the disease is taken into account by a chemotherapy treatment of the final host (Ritchter et al 1999, Millan et al 2000. No integrated program aiming at stopping or at limiting the transmission of the parasite, associating the control of intermediate snail hosts to other control strategies is currently carried out at the national level.…”
mentioning
confidence: 99%
“…Third, biliary colic and increased liver enzymes do not occur in individuals treated with TCBZ for other indications such as paragonimiasis (58) . Last, ultrasonographic studies of the liver fl uke have shown that the parasites stop moving on posttreatment day 3, and the whole parasite or its fragments are eliminated through the biliary tract, with a transitory increase in the diameter of the biliary duct (59) (60) .…”
Section: Discussionmentioning
confidence: 99%